The intellectuals of the independent academic centers and the rise of Concertacionismo - Mella Polanco, Marcelo (Revista de Historia Social y de las Mentalidades, 2025)
This article analyzes the thought of the intellectuals linked to the Independent Academic Centers (C.A.I.) of the democratic opposition between 1983-1990. At this level we will ask ourselves if there is an ideological matrix that can be designated "concertacionista" for constituting a coherent story, capable of influencing the programmatic proposals, but above all, capable of determining the strategies of the actors of the conglomerate that will come to power. in Chile in 1990. Examining this problem will allow us to identify the degree of originality or continuity of this coalition and define basic elements of its grammar of domination
Keywords: Intellectuals; Independent Academic Centers; Concertanionist ideological framwoek